Generation and characterization of Lhx3GFP reporter knockin and Lhx3loxP conditional knockout mice. Issue 4 (25th March 2018) - Xu, Mei; Xie, Xiaoling; Dong, Xuhui; Liang, Guoqing; Gan, Lin
Abstract: LHX3, a LIM‐homeodomain transcription factor, is broadly expressed in the developing pituitary, spinal cord, medulla, retina and inner ear, and plays essential roles during embryonic development. Mice with homozygous Lhx3 null mutation exhibit failure in the formation of pituitary gland and die perinatally. To facilitate the functional study of Lhx3 in mice, we engineered and characterized two novel Lhx3 mouse strains: Lhx3 GFP reporter knock‐in and Lhx3 loxP conditional knockout mice. Coimmunolabeling of LHX3 and GFP shows that the expression pattern of the knock‐in GFP reporter recapitulates that of endogenous LHX3 in cochlea, vestibule, retina, and spinal cord. By crossing Lhx3 loxP mice with the ubiquitous CMV‐Cre mice, we have demonstrated a high efficiency of Cre recombinase‐mediated removal of exons 3 to 5 of Lhx3, which encode the second LIM‐domain and the HD domain of LHX3, resulting global knockout of Lhx3 . Thus, Lhx3 GFP and Lhx3 loxP mice serve as valuable genetic tools to dissect the tissue‐specific roles of Lhx3 at late‐gestation and postnatal stages in mice.